Numerical Structural Response Analysis of Savonius Wind Turbine Blades with Geometric Variation under Aerodynamic Loads - Sudjono, Aldo Alfattah; Sari, Delima Yanti; Syahril, Syahril; Rifelino, Rifelino (invotek, 2025)
Rising demand for electrical energy has accelerated the development of renewable energy technologies, including wind turbines designed to operate at low wind speeds. The savonius vertical-axis wind turbine is a promising option due to its simple configuration and insensitivity to wind direction. Nevertheless, the structural reliability of its blades is strongly affected by their geometry and the material selected. This study focuses on evaluating the structural response of savonius turbine blades under aerodynamic loading using the finite element analysis (FEA) method. Simulations were carried out in ANSYS Workbench R2 2025, considering geometric variations in blade thickness (1.2 mm, 1.5 mm, and 2 mm), aspect ratio (0.8, 1.0, and 1.3), and arc angle (120°, 150°, and 180°). The blades were modeled using AISI 304 stainless steel. The analysis examined von mises equivalent stress, total deformation, and safety factor. The analysis results show that all geometric variations are structurally safe with a safety factor value of 15. The highest maximum von mises stress of 0.081 MPa occurs at a thickness of 1.2 mm, while the lowest value of 0.017 MPa is obtained at an arc angle of 180°. The maximum deformation of 3.38 × 10⁻³ mm occurred at an arc angle of 150°, while the lowest deformation of 6.77 × 10⁻⁴ mm was obtained at an arc angle of 180°, which indicates the most structurally stable configuration.